Akselerasi Teknologi Asisten Guru melalui Pengembangan Virtual Teacher Hologram Berbasis Rapid Rural Appraisal dan MDA Framework - Purnamasari, Ica; Choiro, Umu Da'watul; Listyaningrum, R. Anggia; Surya, Eka Putri; Marcelliantika, Adinda; Aruna, Alby (IAI Nasional Laa Roiba Bogor, 2024)
This article discusses the acceleration of teacher assistant technology through the development of a Virtual Teacher Hologram based on Rapid Rural Appraisal (RRA) and the MDA Framework. This community service program aims to improve the quality of education in rural areas by utilizing hologram technology as a virtual teacher assistant. The methodology includes Rapid Rural Appraisal to identify educational needs and the MDA Framework to design and implement hologram technology. The results indicate that the use of the Virtual Teacher Hologram significantly enhances student interaction, comprehension of materials, and the overall quality of education in rural areas. Additionally, this technology facilitates more equitable and quality access to education. In conclusion, the development of the Virtual Teacher Hologram based on RRA and the MDA Framework provides a positive contribution to accelerating educational technology in rural areas.